SELEKSI FENOTIPE DAN MOLEKULER GALUR GALUR PADI (Oryza sativa L.) LOKUS PUP1 DAN ALT PADA LARUTAN HARA YOSHIDA - Tri Lestari Novelia; Joko Prasetiyono; Sulastri Isminingsih; Samsu Hilal (Jurnal Agroekoteknologi, 2019)
ABSTRACTThis research aimed to selection the phenotype and molecular of rice lines (Oryza sativa L.) containing Pup1 and Alt loci at various concentrations of Al and P elements in yoshida nutrient solution. This research was conducted from November 2018 to February 2019 at The Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development Bogor. The phenotype study used a Split Plot Design with two factors and repeated three times. The first factor was the variation of Al×P concentrations consisting of eight levels and the second factor was the variation of rice lines consisting of twenty levels. The molecular study used three primers to detect the rice lines with Pup1and Alt loci. The results of the Yoshida nutrient solution showed that the A4 level of Al×P concentrations (0 ppm of Al×15 ppm of P) had the best average of other levels. In rice lines with Pup1 loci G4 [10B (B4-SK4)] showed the highest average on the root dry-weight parameters. In rice lines with Pup1 and Alt loci G11 [35(21(B15)-3] showed the highest average on the root dry-weight parameters at the A2 level of Al×P concentrations (0 ppm of Al×5 ppm of P) for Pup1 loci and A6 level of Al×P concentrations (60 ppm of Al×5 ppm of P) for Alt loci. In the molecular study, three primers can detect the rice lines that contained Pup1 and Alt loci. K46-2 specific primer detected the Pup1 loci with thecomparison of Kasalath rice variety. RM12031 and RM1361 primers detected the Alt loci with the comparison of Dupa rice variety.